Comparison of the Effectiveness of 5 Iu Oxytocin Bolus and 20 Iu Infusion on Uterine Contraction and Hemodynamic Response in Caesarean Section - Aidyl Fitrisyah; Rose Mafiana; Agustina Br. Haloho; Theodorus (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Uterine atonic can result in postpartum hemorrhage, gravid hysterectomy and maternal mortality. Oxytocin is the most commonly used agent for the prevention and treatment of atonic uterine during cesarean section. However, the provision of rapid and increasing the dose may result in hemodynamic instability, cardiovascular collapse, and death. This study aimed to compare the effectiveness of oxytocin bolus 5 IU and oxytocin infusion 20 IU to contractions of the uterus and the hemodynamic response in cesarean section with spinal anesthesia.An experimental study, Randomized Controlled Trial (RCT) was conducted in the operating room Mohammad Hoesin Hospital Palembang from July to August 2016. It was obtained a 44 pregnant at term women who will do a cesarean section that meet the inclusion and exclusion criteria. The frequency and distribution of data are described in tables and comparisons between the two groups were analyzed using SPSS.Of the 44 pregnant women at term, 22 women in the group of oxytocin bolus 5 IU and 22 women in the group of oxytocin infusion 20 IU. By statistical analysis, there was no significant hemodynamic changes after bolus administration of oxytocin 5 IU or oxytocin infusion 20 IU (p> 0.05) and there were no significant hemodynamic differences between oxytocin bolus 5 IU and infusion of 20 IU oxytocin (p> 0.05). In addition, there are significant changes in uterine contractions after bolus administration of oxytocin 5 IU or oxytocin infusion 20 IU (p< 0.05) and there were significant differences in uterine contraction in the 3rd minute (p = 0.006), 6th minute ( p = 0.010) and 9th minute (p = 0.008) between oxytocin bolus 5 IU and infusion of oxytocin 20 IU.It can be concluded that there is no significant hemodynamic changes after administration of oxytocin 5 IU bolus and oxytocin infusion 20 IU and there are differences in uterine contractions significantly in the 3rd minute, 6th minute and 9th minute between oxytocin bolus 5 IU and oxytocin infusion 20 IU.